MENINGKATKAN KEMAMPUAN PENALARAN DAN HASIL BELAJAR MATEMATIKA SISWA SMK DENGAN PEMBELAJARAN PROBLEM SOLVING - Yudi Prasetio; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to identify and describe an increase in reasoning and student learning outcomes in mathematics learning with problem solving learning. This research is a class research or Classroom Action Research (CAR). The research subjects who acted were students of Class XI of Jabir Al-Hayyan Vocational School, amounting to 30 students, while the object of the research was mathematical reasoning and student learning outcomes. Methods of collecting data through observation, testing, documentation, and field notes. Data analysis techniques in descriptive qualitative flow models. Data validity using triangulation technique is source triangulation and method. Based on these results, it was obtained: 1) Improving students' mathematical reasoning can be seen from increasing indicators which include, among others: a) The ability to think logically before the action by 30%, increase to 63.33% in cycle 1 and cycle 2 increases to 76.67%, b) The ability to think critically before the action was 26.67%, increased to 56.67% in the first cycle, and the second cycle increased to 70%, c) The ability to draw conclusions before the action by 20%, increased to 46.67% in the first cycle and the second cycle increased to 63.33%, 2) improving students' mathematics learning outcomes which can be seen from the results of written tests that met the value of ≥ 75 before the action by 43.33%, increasing to 63 , 33% in cycle 1 and cycle 2 increases to 80%. This study concludes that learning problem solving when learning mathematics can improve students' reasoning and learning outcomes.